Evaluation of high intensity focused ultrasound treatment for different types of adenomyosis based on magnetic resonance imaging classification - Chunmei Gong; Yangyang Wang; Fajin Lv; Lian Zhang; Zhibiao Wang (International Journal of Hyperthermia)
Objective To evaluate the mid-term symptom improvement of patients with different types of adenomyosis based on magnetic resonance imaging (MRI) classification after ultrasound-guided high intensity focused ultrasound (USgHIFU) treatment.Materials and methods A total of 321 patients with adenomyosis who underwent HIFU and completed 18-month follow-up were retrospectively reviewed. Based on the relationship between the adenomyotic lesion and the uterine structural components on T2-weighted imaging (T2WI), adenomyotic lesions were classified as internal, external, full thickness and intramural adenomyosis. Based on the extent of the myometrial involvement, these lesions were further subclassified as asymmetric and symmetric adenomyosis.Results All patients completed HIFU ablation in one session. The range of median menstrual pain score in patients with asymmetric internal, symmetric internal, asymmetric external, asymmetric full thickness, symmetric full thickness, and intramural adenomyosis was between 6 and 8 points before HIFU, the median menstrual pain score decreased to 2–4 points 18-month post-HIFU (p < .005). The menstrual pain relief rate was 68.3%, 62.1%, 54.7%, 64.1%, 60%, and 100%, respectively. The median menstrual blood volume score range was between 2 and 4 points in the different groups of patients before HIFU, it decreased to 1–3 points 18-month after HIFU with a relief rate of 68.3%, 51.6%, 51.0%, 55.5%, 57.2%, and 100%, respectively. No serious complication occurred in any of these patients.Conclusions Based on our results, USgHIFU is safe and effective in the treatment of patients with different subtypes of adenomyosis with mid-term sustained improvement in symptoms of menstrual pain and menstrual blood volume.